2018
DOI: 10.1134/s1607672918020151
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Encoding the Universal Stress Protein AtUSP is Regulated by Phytohormones and Involved in Seed Germination of Arabidopsis thaliana

Abstract: For the first time, the organ-specific expression pattern of the AtUSP (At3g58450) gene, which also undergoes hormonal regulation, was shown. The USP protein encoded by this gene is involved in seed germination of Arabidopsis thaliana and, unlike abscisic acid, stimulates this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It was found that AtUSP functions as a molecular chaperone under oxidative, heat, and cold-shock conditions (Jung et al 2015;Melencion et al 2017). Gorshkova et al (2018) indicated that AtUSP is regulated by phytohormones and is involved in seed germination of Arabidopsis. The role of USPs in maintaining black poplar seed longevity could be associated with chaperon activity, but that should be verified in future experiments.…”
Section: Proteins Involved In Stress Responsesmentioning
confidence: 99%
“…It was found that AtUSP functions as a molecular chaperone under oxidative, heat, and cold-shock conditions (Jung et al 2015;Melencion et al 2017). Gorshkova et al (2018) indicated that AtUSP is regulated by phytohormones and is involved in seed germination of Arabidopsis. The role of USPs in maintaining black poplar seed longevity could be associated with chaperon activity, but that should be verified in future experiments.…”
Section: Proteins Involved In Stress Responsesmentioning
confidence: 99%
“…In Arabidopsis , overexpression of USP has been shown to enhance resistance to oxidative stress and fungal pathogen attack [9,12]. In addition, the USP promoter region is reportedly regulated by seed germination‐related phytohormones and abiotic stress responses [13,14]. The closest homolog of USP in Arabidopsis , Hypoxia Responsive Universal Stress Protein 1 ( HRU1 ), mediates reactive oxygen species (ROS) homeostasis signaling under anoxic conditions by sensing the level of oxygen [15].…”
mentioning
confidence: 99%
“…GRUSP protein (Germination-Related Universal Stress Protein) encoded by At3g58450 gene A. thaliana [ 12 , 13 ] is a potential member in pathways controlling the balance between ABA and GA throughout different growth stages. At3g58450 expression significantly increases in Col-0 seedlings treated with ABA, and impairment of its transcription causes ABA hypersensitivity of transgenic seeds grusp-115 [ 12 ].…”
mentioning
confidence: 99%
“…In this study, we used A. thaliana (L.) Heynh ecotype Columbia wild type (Col-0) and GABI_kat 115C08 ( grusp-115 ) homozygous transgenic line [ 12 ]. Plants were grown in a chamber with a controlled environment at 16-h photoperiod, light intensity of 100 μmol m –2 s –1 and temperature +21°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation